High Efficient Visible-Light Photocatalytic Performance of Cu/ZnO/rGO Nanocomposite for Decomposing of Aqueous Ammonia and Treatment of Domestic Wastewater - He, Shiying; Hou, Pengfu; Petropoulos, Evangelos; Feng, Yanfang; Yu, Yingliang; Xue, Lihong; Yang, Linzhang (Frontiers in Chemistry, 2018)
Photocatalytic removal of ammonium-nitrogen (NH4+-N) from water using solar energy is an approach of high interest and applicability due to the convenience in application. ZnO has a great potential in photocatalytic decomposition of NH4+-N and conversion of this nutrient to under visible light irradiations. However the applicability of pristine ZnO though is limited due to its reduced capacity to utilize light from natural light. Herein, we report a two-step ZnO-modified strategy (Cu-doped ZnO nanoparticles, immobilized on reduced graphene oxide (rGO) sheets) for the promotion of photocatalytic degradation of NH4+-N under visible light. UV-Vis spectra showed that the Cu/ZnO/rGO can be highly efficient in the utilization of photons from the visible region. Hence, Cu/ZnO/rGO managed to demonstrate adequate photocatalytic activity and effective NH4+-N removal from water under visible light compared to single ZnO. Specifically, up to 83.1% of NH4+-N (initial concentration 50 mg•L−1, catalyst dosage 2 g•L−1，pH 10) was removed within 2 h retention time under Xe lamp irradiation. From the catalysis, the major by-product was N2. The high ammonia degradation efficiency from the ZnO/Cu/rGO is attributed to the improvement of the reactive oxygen species (ROSs) production efficiency and the further activation of the interfacial catalytic sites. This study also demonstrated that such nanocomposite is a recyclable agent. Its NH4+-N removal capacity remained effective even after five batch cycles. In addition, Cu/ZnO/rGO was applied to treat real domestic wastewater, and it was found that chemical oxygen demand (COD), total nitrogen (TN) and total phosphorus (TP) removal efficiencies can reach 84.3, 80.7% and 90.3%, respectively. Thus, Cu/ZnO/GO in the presence of solar light can be a promising photocatalyst in the field of wastewater treatment.